2016
DOI: 10.1016/j.epsl.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Immiscible iron- and silica-rich liquids in the Upper Zone of the Bushveld Complex

Abstract: The Bushveld Complex (South Africa) is the largest layered intrusion on Earth and plays a considerable role in our understanding of magmatic differentiation and ore-forming processes. In this study, we present new geochemical data for apatite-hosted multiphase inclusions in gabbroic cumulates from the Bushveld Upper Zone. Inclusions re-homogenized at high-temperature (1060-1100 • C) display a range of compositions in each rock sample, from iron-rich (35 wt.% FeO tot ; 28 wt.% SiO 2 ) to silica-rich (5 wt.% FeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…Notably, the top portion (>4000 m above the MR, <35% liquid remaining) of the analyzed stratigraphy displays scattered measured values not mirrored by our estimations (Figure 6). VanTongeren and Mathez [2012] proposed that the uppermost 625 m of the Upper Zone underwent large-scale silicate liquid immiscibility, and the study of Fischer et al [2016] identified the presence of both Fe-rich and Si-rich melt inclusions trapped in apatite grains within the Upper Zone. Our data within the potential liquid immiscibility portion do follow markedly different trends than the data below it ( Figure 5).…”
Section: Comparison Of Modeled and Measured D 56 Fementioning
confidence: 99%
“…Notably, the top portion (>4000 m above the MR, <35% liquid remaining) of the analyzed stratigraphy displays scattered measured values not mirrored by our estimations (Figure 6). VanTongeren and Mathez [2012] proposed that the uppermost 625 m of the Upper Zone underwent large-scale silicate liquid immiscibility, and the study of Fischer et al [2016] identified the presence of both Fe-rich and Si-rich melt inclusions trapped in apatite grains within the Upper Zone. Our data within the potential liquid immiscibility portion do follow markedly different trends than the data below it ( Figure 5).…”
Section: Comparison Of Modeled and Measured D 56 Fementioning
confidence: 99%
“…Co-existing Fe-and Si-rich melt inclusions (e.g., Fischer et al 2016;Jakobsen et al 2005Jakobsen et al , 2011Luais 1987;Roedder and Weiblen 1970) and Fe-rich droplets dispersed in Si-rich glassy mesostasis in rapidly cooled natural examples (e.g., De 1974;Philpotts 1982;Philpotts and Doyle 1980) provide evidence of immiscibility in ferrobasaltic liquid. The physical behaviour of these immiscible liquids in a crystal mush may play an important role in the evolution of mafic intrusions, particularly if there is relative movement of the two liquids (e.g., Holness et al 2011;VanTongeren and Mathez 2012;Zhou et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other processes, such as inducing spinel oversaturation by magma oxidation, are similarly rather difficult to assess and have not been much tested directly, but have been proposed for other intrusions based on stable isotopic evidence for carbonate assimilation which has stimulated either chromite and sulphide saturation in the Uitkomst Complex (Gauert 2001) or magnetite oversaturation in the Panzhihua layered mafic intrusion (China) (Ganino et al 2013). The concept of immiscible metal-rich liquids, proposed but discarded early on in evaluations of evolved Bushveld rocks (Reynolds 1985), has reemerged in light of studies of thick Fe-Ti-V oxide deposits in China over the past decade or so (Zhou et al 2013;Fischer et al 2016;Nielsen et al 2017).…”
Section: Geoscience Canadamentioning
confidence: 99%